Reproducción inducida del sábalo cola roja Brycon cephalus (Günther, 1869). Amazonía peruana: Iquitos - Babilonia Medina, Jorge (2014)
The experiment was conducted at the Aquaculture Station “Amazonia Aquaculture Service”. We worked with 13 females and 16 males. The main objectives was the inducing breeding with carp pituitary extract. All females spawned, however, five females with negative results on fertility. In an average temperature of 28.12±0.61 °C, it takes 5.68±0.53 hours for spawning or 159.01±14.45 hours-grade. The females of 4 years of 2310±143.2 g, fertilization rate achieved, over 66% on average 1497.60±14,57 eggs are per gram, fertilization and hatching rate of 68.80±1.9% and 53.59±8.7% respectively. Hatching occurred at 11.67±0.32 hours, the water temperature was 28.25±0.09 °C, so that the hatching 331.07±12.56 required hour’s degree.